S Signifikansi Bimbingan Pranikah Terhadap Keharmonisan Rumah Tangga Kristen Pada Keluarga Kristen di Gereja Kemah Injil Indonesia Jemaat Mongga Rote Ndao - Johana Betris Tumbol; Sarce Rien Hana; Yeane Djelita Mesah (Institut Agama Kristen Negeri Kupang, 2022)
The purpose of this study was to determine the effect of premarital guidance on household harmony in Christian families in Gereja Kemah Injil Indonesia jemaat Mongga-Rote Ndao. The sample is 15 married couples aged 3-15 years of marriage. Quantitative research methods. First is a literature review through books and journals, then distributes a questionnaire in the form of a google form to get research data. Interviews to support the questionnaire were conducted by telephone. The research analysis uses the percentage technique and is presented in the form of tables and simple correlation analysis. The results showed that there was a positive influence of premarital guidance on household harmony with a simple correlation coefficient interpretation value of 0.788 which was classified as strong. Thus it can be concluded that the premarital guidance that is carried out can have a strong influence on household harmony